Contribution Analysis of Cognitive Behavior Theraphy Approach in Group Guidance to Student Bullying Behavior - Amelia, Fahriza; Lesmana, Gusman (Lembaga Riset Mutiara Akbar, 2022)
This study uses a quantitative approach with a quasi-experimental type by looking at changes in research data between before and after being given treatment. The population in this study was 40 students of class XII then the sampling technique used purposive random sampling. The results of the reliability test of the bullying behavior character instrument were 0.911. The research data were analyzed using the Wilcoxon test. The research findings show that the correlation obtained from the SPSS output model summary 26.00 shows the magnitude of the results of the hypothesis test with the Wilcoxon test, the output is 2.807b with the value of Asymp.Sig. = 0.005 (2-tailed) is less than < 0.005, then Ha is accepted. Here there are 10 positive data (N) which means that 10 students experienced a decrease in bullying behavior from the Pre-Test value to the Post Test value. The mean rank or average increase is 5.50, while the number of positive rankings or the sum of Ranks is 55.00. Thus, it can be concluded that the application of the cognitive behavior therapy approach in group guidance can have an influence on the decline in bullying behavior of students at SMK Persatuan Amal Bakti 3 Medan TA. 2021/2022